Phytoplankton taxonomic composition, nutrients utilization and biogeochemistry in the upper mixed layer in the coastal area of the Terra Nova Bay, Ross Sea, Antarctica - Massi, Luca; Nuccio, Caterina; Melillo, Chiara; Becagli, Silvia; Mori, Giovanna; Verdiani, Lorenzo; Bonamano, Simone; Madonia, Alice; Piermattei, Viviana; Marcelli, Marco; Lazzara, Luigi (Frontiers in Marine Science, 2025)
Within BioAPRoS project (Biogenic Aerosol and Primary production in the Ross Sea) two research campaigns were conducted in the coastal area of Terra Nova Bay (TNB) in front of the Italian Base Mario Zucchelli Station, Ross Sea, Antarctica, spanning from 13/11/2018 to 30/01/2019 (BioAPRoS18), and from 01/12/2019 to 30/01/2020 (BioAPRoS19), an area classified as Marginal Ice Zone (MIZ) during this period. The goal was to study nutrient dynamics, phytoplankton biomass and taxonomic composition in the upper mixed layer (UML), exploring assimilation preferences of different phytoplankton assemblages and their biogeochemical effects. The findings were compared with similar 1990s campaigns in the same region. In line with the previous outcome, UML was persistent and always very shallow (5-18 m). Nutrient concentrations showed decreasing trends from spring to summer synchronously opposite to Chla, highlighting pronounced consumption of nutrients during phytoplankton growth. Discrepancies emerged during phytoplankton summer bloom; in BioAPRoS18 N/P was about 40 due to ΔN/ΔP removal ratio of 11.8, a typical already known condition, while BioAPRoS19 showed an unprecedented N/P around 6 with ΔN/ΔP of 17.6. Also, differences in Si/P and Chla/Si ratios emerged. Diatoms were the primary group in both campaigns, but they exhibited highly differentiated composition. In BioAPRoS18 pennate diatoms, notably Fragilariopsis curta, were prevalent as in ‘90s campaigns, while BioAPRoS19 experienced the dominance of centric diatoms, especially Dactyliosolen tenuijunctus, never occurred before. These differences in nutrients dynamics and taxonomic composition between the two diatom assemblages, most likely indicate different assimilation modalities of N and P, with Dactyliosolen tenuijunctus favouring N assimilation over P, unlike Fragilariopsis curta. Biological and biogeochemical characteristics of TNB, a pivotal marine ecosystem, are then displaying shifts after relative stability since the 1990s that could be the result of current climate change. These trends necessitate in-depth investigations and monitoring to comprehend and manage these shifts effectively.